Packaging design tool: The effectiveness of opening indications for older people - Chavalkul, Yada (Humanities, Arts and Social Sciences Studies, 2023)
Packaging with a novel appearance and opening method is a powerful marketing strategy. However, accessibility to products can be limited for older consumers due to unfamiliarity with how to open the packaging. This research evaluated the outcomes of a previous study regarding design tools that determined the ease of instructions explaining opening methods of novel packaging for older people. This manuscript is structured into two phases. Phase one evaluates a diagram identifying the effectiveness of opening directions. A triangulation investigation was conducted to compare the evaluations from a researcher, designers, and 36 older participants. The researcher and designers used the diagram to examine the opening instructions of five packages, while older participants opened the packages to help investigate the clarity of the given directions. The results were inconsistent; therefore, the diagram to identify the effectiveness was unreliable. Accordingly, the researcher revised the diagram and combined it with the packaging design tool, utilizing the data from three designer focus groups and older participants’ in-depth interviews. The final design tool was a step-by-step checklist guiding designers to analyze opening indications, then identify design problems. Phase two centered on examining two aims: to assess the revised design tool used for creating effective opening directions for older people and to formulate considerations for developing the design tool. Twelve designers applied the design tool to redesign the misleading directions of two packages. It was found that of the two directions for opening the redesigned packages, one was easier to understand for the older participants than the other. The design tool was efficient when the package adopted simple directions. The design tool improvement considered its contents—balancing between thorough checklists and overloading contents; its method—recognizing the difference between older people’s and designers’ cognition regarding opening indications; and its form—applying graphic-oriented design.